The frozen elephant trunk technique in acute aortic dissection: the ultimate solution? An institutional experience - Wisniewski, K.; Dell’Aquila, A. M.; Motekallemi, A.; Oberhuber, A.; Schäfers, J. F.; Marchiori, E.; Weber, R.; Martens, S.; Rukosujew, A. (Frontiers in Cardiovascular Medicine, 2024)
Objective Acute aortic dissection remains a serious emergency in the field of cardiovascular medicine and a challenge for cardiothoracic surgeons. In the present study, we seek to compare the outcomes of different surgical techniques in the repair of type A acute aortic dissection. Methods Between April 2015 and May 2023, 213 patients (82 women, aged: 63.9 ± 13.3 years) with acute aortic dissection (205 type A and 8 non-A-non-B dissections) underwent surgical treatment in our department. A total of 45 patients were treated with the frozen elephant trunk (FET) technique supported by the Thoraflex™ Hybrid prosthesis, 33 received total aortic arch replacement (TAR)—standard or conventional elephant trunk—treatment, and 135 were treated with hemiarch replacement (HR). Aortic arch surgery was performed in most patients under moderate hypothermic (28°C on average) circulatory arrest, with selective antegrade cerebral perfusion through the right axillary artery. Results The rates of early mortality were 17.8% (38 perioperative deaths) in the whole population, 8.9% in the FET group of patients, and 33% and 17% in the TAR and HR group of patients, respectively (P-value 0.025). The rate of spinal cord injury was 2.3% (five patients), and a paresis of recurrent laryngeal occurred in 3.7% of patients (seven patients, four were treated with FET). Permanent neurological dysfunction occurred in 27 patients (12.7%). After a mean follow-up of 3 years, the rate of mid-term mortality of discharged patients was 19.4% (34 deaths: 7 FET, 4 TAR, and 23 HR) and the overall mortality rate was 33.8% [72 deaths: 11 FET (24.4%); 15 TAR (45.4%); 46 HR (34.1%)]. A total of 8 patients (17.8%) in whom FET was applied received additional endovascular treatment in the descending aorta. Conclusions In our institutional experience, we found that the frozen elephant trunk technique with a high-end Thoraflex Hybrid prosthesis proved its surgical suitability in the treatment of acute aortic dissection with favorable outcomes. The FET technique and our perioperative management led to comparable neurological outcomes and reduced mortality rates in these emergency cases.